Faktor–Faktor Penentu Keberhasilan Pelepasliaran Orangutan Sumatera (Pongo Abelii) di Taman Nasional Bukit Tigapuluh - Yanto Santosa; Julius Paolo Siregar; Dones Rinaldi; Dede Aulia Rahman (Jurnal Ilmu Pertanian Indonesia, 2012)
Study on determinant factors on success of Sumatran orangutan reintroduction was done to all orangutans in reintroduction station (84 individual + 1 infant orangutan). This study was conducted from August to December 2006 in the Station of Orangutan Reintroduction Centre located in Buffer Zone of Bukit Tiga Puluh National Park. The purpose of this study was to measure the effects of determining factors to the success of orangutans reintroduction to their natural habitat and to identify other factors that give impact to the reintroduction success. Data were collected through direct observation of activities and daily behavior of orangutans using scan sampling and continuous recording methods as well as through interviews with officials. Data analysis was performed descriptively and quantitatively using statistical tests (chi–square) with 95% confidence interval. The results showed that there is a match between percentage of success of the reintroduction of the six criteria of reintroduction success. The results of chi–square indicates that determinant factors, such as age class, orangutan life history, treatment and duration of reintroduction stage, are correlated to the success of reintroduction activities.